Same assignment—two different feedback contexts: lower secondary students’ experiences with feedback during a three draft writing process - Moltudal, Synnøve Heggedal; Gamlem, Siv M.; Segaran, Meerita; Engeness, Irina (Frontiers in Education, 2025)
This study explores students’ conceptions and experiences with feedback as integrated parts of a three draft writing process and group discussions in English as a foreign language (EFL) in three schools. The students (n = 106, six classes) were following the same draft writing process design during a full school day. The same assignment was given to all participating students, but different feedback contexts were assigned in each school. Half of the students received AI-generated feedback (context 1), while the remaining received peer feedback (context 2). Observations were conducted in all classes during the writing assignment. Individual interviews with students (n = 22) were used to investigate students’ experiences during the draft writing process, and the interviews were thematically analyzed. We find that while AI-generated feedback information supported students dialogic feedback interactions the peer feedback context allowed for students to rehearse their assessment and feedback strategies. The study also reveals that peer feedback for lower secondary school students is challenging, since the students function as both feedback givers, receivers and users during the draft writing process. Key aspects regarding how the students engaged with AI-generated feedback and peer feedback are discussed and we find that both feedback contexts have the potential to develop feedback literacy among lower secondary school students. Our study can contribute to the growing understanding of the relationship between feedback contexts, lower secondary students’ uptake of feedback, and how feedback literacy could be developed.